Religion und Pandemie Staat, Religion und Gesellschaft in Saudi-Arabien und Iran in der Coronakrise - Heuvel, Noël van den (Geschichte und Gesellschaft, 2020)
Religious communities have acted as vectors for the spread of the novel coronavirus. This observation might suggest that the crisis has sparked a confrontation between scientific rationalism and (irrational) belief. Using the two decidedly Islamic countries Saudi Arabia and Iran as examples, the article argues however that the relationship between religion and science is far more complex. While Iran has tried to keep its shrines open to the public, Saudi Arabia has halted visits to Muslim holy sites. Both responses were grounded in religious justifications. The reasons for each country’s different course of action can be found in their histories, as well as in differences in religion and the relationship between religion and the state.